A multi-scalar classification system for the terrestrial vegetation of the world - Javier Loidi (Vegetation Classification and Survey (VCS))
An approach is proposed for a general multiscale classification of terrestrial vegetation applicable to the whole world; only the outline and principles are presented. Further development of the system should take place through future national and regional surveys. As in other proposals, there are several levels in this system, of which the upper ones are broad and cover large areas, while the lower ones have a local character. To distinguish it from other approaches, this classification is based on clearly defined and hierarchically sorted criteria: Climate, physiognomy, zonality and biogeography for the upper levels, and site conditions and disturbance, reflected by their floristic composition, for the lower ones. The upper level units are created using a top-down (deductive) approach, while the lower level units are created using a bottom-up (inductive) approach, using the Braun-Blanquet classification as a model for the areas where it is available. Both trestles overlap at level 3: Regional Subbiomes, which are the result of the division of Subbiomes (level 2) and can be underpinned by units of phytosociological classes at level 4. Only the zonal and intrazonal classes can be used for this, as the azonal and those conditioned by disturbance use to exceed the scope of a particular zone. Syntaxonomic references: Mucina et al. (2016) for high rank syntaxa, with the exception of Querco-Fagetea and Fagetalia sylvaticae which follow Loidi (2020); Rivas-Martínez et al. (2011a) for low rank syantaxa (alliances and associations); Rivas-Martínez (1997) for Heteromelo arbutifoliae Quercetea agrifoliae; Krestov et al. (2023) for Quercetea mongolicae and Miyawaki et al. (1964) for Fagetea crenatae.